Doubling Down on Asia Victor D. Cha, Power Play: The Origins of the American Alliance System in Asia (Princeton University Press, 2016). Michael R. Auslin, The End of the Asian Century: War, Stagnation and Risks to the World's Most Dynamic Region (Yale University Press, 2017). - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2018)
With the Chinese government aggressively militarizing the South China Sea and U.S. President Donald Trump scuttling the Trans-Pacific Partnership, there appears no clear answer to Beijing’s “One Belt, One Road” initiative. In fact, U.S. foreign policy thinkers are casting about for a strategy in Asia. What is to be done? Victor Cha’s Power Play and Michael Auslin’s End of the Asian Century recommends that the United States “double-down,” an expression Cha uses repeatedly, on its time-tested strategy of containing Chinese power in Asia.